INTEGRATION OF CODING AND ARTIFICIAL INTELLIGENCE IN INDONESIAN HIGH SCHOOLS: A CASE STUDY IMPLEMENTATION IN URBAN AND RURAL SCHOOLS - Agus Hendri Yaman Telaumbanua; Hotmaulina Sihotang (RADJA PUBLIKA, 2025)
This study aims to analyze the implementation of coding and artificial intelligence (AI) integration in Indonesian high schools by comparing urban and rural schools. The background of this study is the demands of 21st-century digital literacy, which places coding and AI as essential skills for the younger generation. The research method used a case study with a qualitative approach through interviews, observations, and document analysis in two representative high schools. The results show that urban schools are better prepared to integrate coding and AI thanks to adequate infrastructure, stable internet access, and trained teachers. In contrast, rural schools face limited facilities, weak internet connections, and a lack of competent human resources. However, teacher creativity and local community support play a crucial role in bringing digital innovation to students. This study confirms that the success of coding and AI integration is determined not only by technology, but also by educational policies, teacher capacity building, and adaptation of learning strategies to the school context. These findings can provide input for policymakers in promoting equitable digital education in Indonesia.